Diversifikasi Pendapatan pada Industri Perbankan di Indonesia : Implikasi terhadap Kinerja dan Risiko - Sudaryanti, Dedeh Sri; Yuniasih, Yuyun; Kurniawati, Ane (JURNAL AKUNTANSI, 2024)
This research was conducted as an analysis of the effect of income diversification on bank performance and risk. The samples used are banks owned by the central and regional governments in Indonesia for the period 2015 to 2022. Hypothesis testing applies panel data linear regression estimation. Income diversification is measured using the Herfindahl Hirschman Index (HHI) approach, bank performance using Return on Assets, bank risk using ROA standard deviation, and applying two control variables, namely company size and loan to total assets.The research results show that income diversification has a negative influence on bank performance. These state-owned banks often do not implement strategies outside their core business because owners view profit fluctuations as a threat to their ability to supervise. The larger the company size, the ROA tends to be lower, that large banks may have difficulty achieving high ROA due to their more complex operations. The higher the LTA, the higher the ROA tends to be. This could provide an indication that banks are more aggressive in disbursing credit relatively more efficiently in generating profits. Evidence was found that income diversification negatively influences bank risk, indicating that there is a reduction in risk when banks diversify income